The protection of women in armed conflicts: Reflections from the perspective of International Law - García Ganoza, Carmela Sofía (2021)
This paper aims at addressing the protection of women during armed conflicts in International Law, taking into account the different roles that women can have in these contexts as well as the differentiated impact of armed conflicts on women. For this purpose, the author discusses first the notion of violence against women and its diverse manifestations during armed conflicts. Secondly, the author analyses International Humanitarian Law’s provisions designed to protect women, as well as the criticisms and limitations of said regulation. Lastly, the article presents contributions made by other branches of International Law, such as International Criminal Law, International Human Rights Law and the work of the United Nations Security Council, considering that not only do they complement International Humanitarian Law, but also allow to widen the scope of protection awarded to women in armed conflicts.